2011
DOI: 10.5194/acp-11-955-2011
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl in the stratosphere and mesosphere – Part 1: Diurnal variability

Abstract: Abstract. Diurnal variations in hydroxyl (OH) in the stratosphere and mesosphere are analyzed using measurements from the Aura Microwave Limb Sounder (MLS). The primary driver for OH diurnal variations is the ultraviolet actinic flux that initiates the photochemical production of reactive hydrogen species. The magnitude of this flux is governed largely by changes in solar zenith angle (SZA) throughout the day, and OH diurnal variations are well approximated by an exponential function of the secant of SZA. Meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This is consistent with our initial assumption regarding injecting in a location where fewer aerosols from the previous year are present. Chemical characteristics of the stratosphere at the time of the injection (in particular OH, which oxidizes SO 2 ), which are heavily dependent on the solar zenith angle (Minschwaner et al, 2011), do not appear to correlate with the resulting SO 4 burden (not shown), indicating that the produced AOD is mostly a function of the transport efficiency.…”
Section: Stratospheric Aerosolmentioning
confidence: 99%
“…This is consistent with our initial assumption regarding injecting in a location where fewer aerosols from the previous year are present. Chemical characteristics of the stratosphere at the time of the injection (in particular OH, which oxidizes SO 2 ), which are heavily dependent on the solar zenith angle (Minschwaner et al, 2011), do not appear to correlate with the resulting SO 4 burden (not shown), indicating that the produced AOD is mostly a function of the transport efficiency.…”
Section: Stratospheric Aerosolmentioning
confidence: 99%
“…Therefore, atmospheric transport of HO x below 80 km is negligible. For OH, seasonal and solar cycle variability is connected to solar activity together with the seasonal variation of water vapor and ozone in the mesosphere [ Canty and Minschwaner , 2002] whereas the diurnal variability of OH is related to the solar zenith angle (SZA) variation during the day and can be characterized by exponential functions of the secant of SZA [ Minschwaner et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The response was also found in the observed data. The diurnal cycle of OH concentration which reflects a solar zenith angle changes was analyzed by Minschwaner et al (2011). The response of OH from Fritz Peak Observatory (Colorado) to 11-yr solar cycle was reported by Canty and Minschwaner (2002).…”
Section: Introductionmentioning
confidence: 99%